Sold, not bought: Market orientation and technology as drivers of acquisitions of private biotechnology ventures - Renko, Maija; Yli-Renko, Helena; Denoo, Lien (Journal of Business Venturing, 2022)
Acquisitions are an important exit strategy for technology entrepreneurs and investors, but what can technology ventures do to increase their chances of achieving an acquisition? We draw on signaling theory to examine the role that market orientation plays behind acquisitions. We test our hypotheses in a sample of young biotechnology ventures, and our findings are three-fold. First, we show that a target's market orientation is an important direct driver of acquisitions, thus incorporating a marketing perspective into a literature that has hitherto focused primarily on technological and reputational factors. Second, we find a substitutive interaction effect between market orientation and new product development stage, indicating that for exits through acquisitions, a high level of market orientation can compensate for an early stage of product development. Third, a fuzzy-set Qualitative Comparative Analysis (fsQCA) shows that in some contexts, the monopoly power afforded by patents can further amplify the positive effect of market orientation on acquisition likelihood. Taken together, our findings contribute to a more nuanced understanding of how different signals interact, and suggest that technology ventures should invest in market orientation early on in their life cycle.